A Regulation Method of the Carriage Contract in Domestic Legal System - Wesołowski, Krzysztof (PRAWO i WIĘŹ, 2023)
The author aims to find the optimal method of regulating the contract of carriage in domestic law. The author considers the method of independent (single) regulation of this contract, including the implementation into national law of solutions arising from international conventions regulating the contract of carriage in particular branches of transport, the method of regulation by reference to convention law, and the method of incorporation into internal law of provisions taken from international conventions. Having considered the problems resulting from the assumed degree of integration of nationalregulations with the solutions stemming from international law, as well as the unifying or branch character of the regulation, the author argues in favor of adopting a unified regulation, included in the Civil Code, which appropriatelyformulated references to international conventions should accompany.